PERLINDUNGAN HUKUM TERHADAP PEMBERI DAN PENERIMAN LISENSI HAK CIPTA BIDANG MUSIK AND LAGU - , Kristin , SH, Dr. Sulistiowati, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research is aimed at identifying the law protection on the copyright for the songs, the implementation of rights and obligation between the giver and receiver of the licence and the solution for the violation committed by the license receiver. In the copyright laws, the protection for the copyright hasn't been claborated in detail. This is due to the fact that public views the music not only as the means of entertainment. They also consider the music as the mediumwhich manifest itself as economic and social potentials, even as the copyright on the manifestation of politics of a country. From the economic perspective, the copyright on the songs and music is associated with the infinite financial possibility. From the social point of view, the copyright for the songs and music is associated with social status of the owner and the holder of the copyright. Frrom the political perspective, the copyright on the music and songs reflects the extent to which the goverment exers the effort to direct and to arrange the social order. The method of the research was normative and empiric law. The method represents the law research conducted to examine the library literature and secondary data involving the law principles, law systematics, comparison andliterature. Using this method, the researcher explained the basicconceps of copyright law theory, particulary those which were related with the law protection on the giver and taker of copyright on the song and music. Furthermore, the interview was conducted with respondents and informans who were related with the topic of the reseach. The result indicated that there should be an enforcement in regulating the law protection on the giver and taker of the copyright license on the music and song, thus there is law protection and beneficial relationship between the giver and the receiver of the copyright.